Personality Pathways to Impulsive Behavior and Their Relations to Deviance: Results from Three Samples - Lynam, Donald R. (Journal of quantitative criminology, 2004)
The importance of the relation between impulsivity and deviance is well-acknowledged among criminologists. However, differences in the representations of impulsivity, some merely titular and others substantive, may cloud our understanding of these relations. The current study examines the argument, offered by Whiteside and Lynam Pers. Individuals Diff. (2000) 30: 669–689, that there may be four distinct personality pathways through which impulsive behavior may be manifested. Across three samples (two undergraduate, one community), we examine the validity of a four-factor structure of impulsivity, test whether these four pathways manifest divergent relations with various forms of deviant behavior such as crime and substance use, as well as laboratory manifestations of aggressive and impulsive behavior, and examine the invariance of these results across gender. The results support the existence of a four-factor model of impulsivity, the importance of two specific personality pathways in relation to self-reports of deviance (lack of premeditation and sensation seeking), as well as actual behavior, and suggest that these pathways are important for both men and women.